(untitled) (Research, Society and Development, 2022)
Introduction: The mental actions that most affect the population are anxiety and depression, being depression the one that most affects the population and causes the most damage to mental health in the world. During the COVID-19 pandemic, which was decreed by the World Health Organization (WHO) on March 11, 2020, protection measures were taken mainly or social distancing. Isso trouxe various acometimentos ao mundo em geral, such as isolation, fear, death, insegurança among others. These attacks contribute alarmingly to psychological aggravations such as depression. The treatment of depression is performed by anxiolytic and antidepressant drugs. It is proven that in the COVID-19 pandemic the incidence of depression increased, and consequently the consumption of these drugs. Objective: I present this study as an objective to make an analysis of the use of fluoxetine, used during the COVID-19 pandemic as it is considered an alternative. Methodology: Through a narrative review, we used original articles found on the platforms National Library of Medicine - NIH or PubMed and Scientific Electronic Library Online (SCIELO). Conclusion: There was a notorious or large consumption of anxiolytic and antidepressant medications highlighted by the pharmaceutical industry in that fluoxetine is or more used by consumers. Therefore, more in-depth studies are still needed to understand the use and sale of this drug.